Clinical and Experimental Evidence for a Strain-Based Classification of Left Bundle Branch Block-Induced Cardiac Remodeling. (4th November 2022) - Calle, Simon; Duchenne, Jürgen; Beela, Ahmed S.; Stankovic, Ivan; Puvrez, Alexis; Winter, Stefan; Fehske, Wolfgang; Aarones, Marit; De Buyzere, Marc; De Pooter, Jan; Voigt, Jens-Uwe; Timmermans, Frank
Abstract : Background: Septal strain patterns measured by echocardiography reflect the severity of left bundle branch block (LBBB)-induced left ventricular (LV) dysfunction. We investigated whether these LBBB strain stages predicted the response to cardiac resynchronization therapy in an observational study and developed a sheep model of LBBB-induced cardiomyopathy. Methods: The clinical study enrolled cardiac resynchronization therapy patients who underwent echocardiographic examination with speckle-tracking strain analysis before cardiac resynchronization therapy implant. In an experimental sheep model with pacing-induced dyssynchrony, LV remodeling and strain were assessed at baseline, at 8 and 16 weeks. Septal strain curves were classified into 5 patterns (LBBB-0 to LBBB-4). Results: The clinical study involved 250 patients (age 65 [58; 72] years; 79% men; 89% LBBB) with a median LV ejection fraction of 25 [21; 30]%. Across the stages, cardiac resynchronization therapy resulted in a gradual volumetric response, ranging from no response in LBBB-0 patients (ΔLV end-systolic volume 0 [−12; 15]%) to super-response in LBBB-4 patients (ΔLV end-systolic volume −44 [−64; −18]%) ( P< 0.001). LBBB-0 patients had a less favorable long-term outcome compared with those in stage LBBB≥1 (log-rank P =0.003). In 13 sheep, acute right ventricular pacing resulted in LBBB-1 (23%) and LBBB-2 (77%) patterns. Over the course of 8−16 weeks, continued pacing resulted in progressive LBBB-induced dysfunction, coincident with a transition to advanced strain patterns (92% LBBB-2 and 8% LBBB-3 at week 8; 75% LBBB-3 and 25% LBBB-4 at week 16) ( P =0.023). Conclusions: The strain-based LBBB classification reflects a pathophysiological continuum of LBBB-induced remodeling over time and is associated with the extent of reverse remodeling in observational cardiac resynchronization therapy-eligible patients.